Pencitraan “Liyan” Sebagai Musuh Telaah Gerakan Islam Radikal Di Indonesia - Mukhlas, Abdullah Arif (LPPM Sekolah Tinggi Agama Islam Al Azhar, 2010)
This research investigates hizbut tahrir (HTI) and majelis mujahidin Indonesia (HTI), as Islamic fundamentalist groups. The investigation deals thoroughly with three aspect of Islamic fundamentalist movement: (1) its ideological construct (roots) and its objectification, (2) the perception to the “other” as enemy, and (3) its expression to gain the idealism (applying sharia and khilafah). To conduct the investigation this study draws on qualitative research paradigma, which is implemented by the methods of documentation, depth interview and participant observation. The investigation of this research shows the following result. Firstly, HTI and MMI are to be regarded as an axemplar of universalistic religio-political fundamentalist group. This term is coined to suggest that the movement as HTI and MMI as a fundamentalist group is not only based on religious motives but also on political motives with universal orientation. HTI and MMI have as its political target the determination to reestablish the Islamic state of khilafah. In the opinion of them, this institution will constitute a political umbrella for all Islamic ummah. Secondly, HTI dan MMI have a feeling of being under attack coupled with distrust of kafir in friendship or alliance. Thirdly, they have attention to the perpetual conflict between muslims and non-muslims and insistence that it can cease only by non-Muslim submission to a muslim ruler or Islamic law under the status of dhimmi. Kata Kunci: Islam radikal, liyan, pencitraan